2022
DOI: 10.3389/fcimb.2022.967486
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visualization of phagosomal pH manipulation by Cryptococcus neoformans in an immune signal-dependent way

Abstract: Understanding of how intracellular pathogens survive in their host cells is important to improve management of their diseases. This has been fruitful for intracellular bacteria, but it is an understudied area in fungal pathogens. Here we start elucidating and characterizing the strategies used by one of the commonest fungal pathogens, Cryptococcus neoformans, to survive intracellularly. The ability of the fungus to survive inside host cells is one of the main drivers of disease progression, yet it is unclear w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…C . neoformans infection is known to cause phagolysosome membrane permeabilization [ 35 , 113 115 ], which potentially enables access to PA from the host cell cytosol. Moreover, metabolomic evidence in both human and mouse cells indicates that, especially under specific cellular stress conditions, lysosomes can serve as storage sites for amino acids and metabolites, including pantothenic acid, at concentrations reaching up to the micromolar range [ 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C . neoformans infection is known to cause phagolysosome membrane permeabilization [ 35 , 113 115 ], which potentially enables access to PA from the host cell cytosol. Moreover, metabolomic evidence in both human and mouse cells indicates that, especially under specific cellular stress conditions, lysosomes can serve as storage sites for amino acids and metabolites, including pantothenic acid, at concentrations reaching up to the micromolar range [ 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria, PA-auxotroph attenuates virulence in M. tuberculosis but not in Salmonella [111,112], reinforcing existing variations in the composition of the phagolysosome depending on the hosted pathogen. C. neoformans infection is known to cause phagolysosome membrane permeabilization [35,[113][114][115], which potentially enables access to PA from the host cell cytosol. Moreover, metabolomic evidence in both human and mouse cells indicates that, especially under specific cellular stress conditions, lysosomes can serve as storage sites for amino acids and metabolites, including pantothenic acid, at concentrations reaching up to the micromolar range [116,117].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…To analyze the pH alterations in the phagosomes infected with young and old C. neoformans, we used the amine-reactive pH dye Phrodo green AM (P35373, Thermo Fisher Scientific, Waltham, MA, USA) to label the surface of C. neoformans, according to the manufacturer's instructions and adapted from [15,25]. This staining is non-fluorescent at a neutral pH, but then becomes fluorescent at an acidic pH.…”
Section: Phagocytosis Assay Phagosomal Acidification and Phagosomal P...mentioning
confidence: 99%
“…Based on pivotal studies that characterized C. neoformans interactions with macrophages [15], we hypothesized that C. neoformans phagosome interactions impose selection on the C. neoformans population in the host. In this study, we investigated the strategies used by old C. neoformans to thrive inside host macrophages, and we characterized the age-associated virulence factors that contribute to fungal intracellular survival.…”
Section: Introductionmentioning
confidence: 99%
“…How C. neoformans affects the lysosomal maturation pathway is not well understood in DCs, but early studies in macrophages show C. neoformans does not prevent phagolysosome fusion and can survive in an acidic environment [79,80]. However, recent studies, mainly in monocytes and macrophages, have found that C. neoformans is capable of modulating the phagosome's pH and development [77,[81][82][83][84].…”
Section: Initial Degradation and Processing Of Cryptococcus By Dcsmentioning
confidence: 99%